Criticism Of The Nisab Agricultural Zakat in The Indonesian National Mazhab - Wibowo, Hendri Setiyo; Fadhlurrahman, Faiz (NALAR, 2024)
Regulation of the Minister of Religious Affairs Number 52 of 2014 is the current regulation in Indonesia as a reference for zakat calculation procedures, one of which is the agricultural zakat nisab of 653 kilograms of grain. This article aims to examine the agricultural zakat nisab unit. This study uses a normative method with a qualitative juridical approach through a literature study that aims to analyze the suitability between theory and practice and evaluate the policies' relevance. The results of the study show that, first, rice units are more appropriate for use as agricultural zakat nisab units. Second, determining the nisab of grain is potentially burdensome for sharecroppers or farm laborers who, in some cases, are eligible to be zakat recipients. With the changes through the Regulation of the Minister of Religious Affairs Number 69 of 2014 and Number 31 of 2019, the results of this study are increasingly relevant as a reference for academic papers for policymakers, especially in compiling regulations related to agricultural zakat. This article provides an academic contribution to the development of zakat studies and becomes practical input to increase the effectiveness of zakat management in Indonesia.